2021
DOI: 10.7899/jce-20-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of chiropractic students regarding interprofessional health care teams

Abstract: Objective To describe perceptions of knowledge of interprofessional teams and value of interprofessional education (IPE) among 3 distinct years of chiropractic students at 1 chiropractic college. Methods A 24-item cross-sectional survey was administered to 247 chiropractic students in years 1–3 within a single institution. Surveys included 5 demographic questions and the 19-item Readiness for Interprofessional Learning Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“… 24 IPL has been reported to have a range of benefits in relation to integrated patient care, professional identity, communication, and teamworking across a range of disciplines. 25 , 26 , 27 Knieper et al 28 have identified the need for chiropractic students to be exposed to IPL opportunities to enhance and enrich the learning experience. Chiropractic students have identified the importance of structured collaborative education in their own health care development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 IPL has been reported to have a range of benefits in relation to integrated patient care, professional identity, communication, and teamworking across a range of disciplines. 25 , 26 , 27 Knieper et al 28 have identified the need for chiropractic students to be exposed to IPL opportunities to enhance and enrich the learning experience. Chiropractic students have identified the importance of structured collaborative education in their own health care development.…”
Section: Discussionmentioning
confidence: 99%
“…Chiropractic students have identified the importance of structured collaborative education in their own health care development. 28 …”
Section: Discussionmentioning
confidence: 99%
“…This finding also suggested the importance of an IPE course on student interprofessional attitude and stereotypes. A study has shown that an effective IPE program could help students feel more willing to engage in interprofessional collaborative activities [40]. For students with less favorable interprofessional attitude, educators should provide information on the roles and responsibilities of nursing in the interprofessional healthcare team through simulations to reduce stereotypes and increase students' respect for nursing profession [41].…”
Section: Factors Affecting Student Stereotypes About Nursingmentioning
confidence: 99%